Cardiovascular efficacy of liraglutide and semaglutide in individuals with diabetes and peripheral artery disease. Issue 7 (11th April 2022) - Verma, Subodh; Al‐Omran, Mohammed; Leiter, Lawrence A.; Mazer, C. David; Rasmussen, Søren; Saevereid, Hans A.; Sejersten Ripa, Maria; Bonaca, Marc P.
Abstract: Aim: To evaluate the cardiovascular (CV) efficacy of liraglutide and semaglutide in patients with type 2 diabetes (T2D) and peripheral artery disease (PAD). Materials and Methods: LEADER and SUSTAIN 6 trials investigated subcutaneous liraglutide (≤1.8 mg/day) and semaglutide (0.5 or 1.0 mg/week), respectively, versus placebo in patients with T2D and high CV risk (median follow‐up: 3.8 and 2.1 years, respectively). The primary outcome was a composite of CV death, non‐fatal myocardial infarction or non‐fatal stroke (major adverse CV event [MACE]) according to the presence of PAD at baseline. Results: Overall, 1184/9340 (12.7%) patients in LEADER and 460/3297 (14.0%) in SUSTAIN 6 had PAD at baseline. Patients with PAD were at an 35% increased risk of MACE versus those without (LEADER: hazard ratio [HR] 1.36, 95% confidence interval [CI] 1.17‐1.58; SUSTAIN 6: HR 1.33, 95% CI 0.94‐1.83). The effects of both therapies on MACE were consistently beneficial in patients with PAD (liraglutide: HR 0.77, 95% CI 0.58‐1.01; semaglutide: 0.61, 0.33‐1.13) and without (liraglutide: HR 0.89, 95% CI 0.79‐1.00; semaglutide: HR 0.77, 95% CI 0.58‐1.01; P interaction = .34 for liraglutide and .49 for semaglutide). Absolute risk reductions for MACE were higher in patients with PAD (liraglutide: 4.13%‐point, 95% CI −0.15‐8.42; semaglutide: 4.63%‐point, 95% CI −0.58‐9.84) versus without (liraglutide:1.42%‐point, 95% CI −0.03‐2.87; semaglutide: 1.90%‐point, 95% CI 0.00‐3.80). Conclusion: Both liraglutide and semaglutide reduce MACE with consistent CV efficacy regardless of PAD status.